1989
DOI: 10.1002/1097-0142(19890601)63:11<2355::aid-cncr2820631147>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a cancer pain model for the testing of long‐acting analgesics. The effect of ms contin in a double‐blind, randomized crossover design

Abstract: A double-blind, double-dummy, crossover study compared oral controlled-release morphine sulfate (MS Contin tablets [MSC], Purdue Frederick, Norwalk, CT) every 12 hours, and immediate-release morphine sulfate (IRMS) tablets, every 4 hours, in 14 evaluable patients with chronic cancer pain. The test model described showed assay sensitivity for steady-state analgesia, requiring relatively few subjects to yield statistical significance in pharmacologic potency estimates. Initial doses were the calculated equivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…8 Some symptoms were more common (but not statistically significant) with liquid morphine (anorexia, dry mouth, flushing, and urinary hesitancy) in our study; unfortunately, these specific symptoms were not evaluated as potential side effects in any prior studies. 16,17,27,28 This pilot study used a previously unevaluated tool with a patient interview technique. The tool closely resembles the traditional symptom review used in routine daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Some symptoms were more common (but not statistically significant) with liquid morphine (anorexia, dry mouth, flushing, and urinary hesitancy) in our study; unfortunately, these specific symptoms were not evaluated as potential side effects in any prior studies. 16,17,27,28 This pilot study used a previously unevaluated tool with a patient interview technique. The tool closely resembles the traditional symptom review used in routine daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A conflicting issue is that the general symptoms in cancer patients with advanced disease (when opioids are frequently prescribed) are also only partially documented. [14][15][16] Although a few prospective studies of individual opioid-related symptoms such as dry mouth 17 and myoclonus 18 have appeared recently, there has been no prospective evaluation of the possible known side effects of morphine during longterm use in cancer patients. We will report the results of a naturalistic 4-week observational study of clinical practice in 30 consecutive patients given morphine in repeated, regular dosing for chronic severe pain due to advanced cancer.…”
mentioning
confidence: 99%
“…The criteria differed for each of these trials and for adequate pain relief included: 'maximum 3 on a 7 point VRS, and not more than two daily requests for rescue analgesia' (Klepstad et al, 2003); 'no need for dose adjustment for three or more days and no morphine sulphate solution intake exceeding 50% of the daily morphine dosage supplied by the test drug' (Deschamps et al, 1992); 'no more than three supplementary doses of immediate release morphine per day' (Portenoy et al, 1989); 'required daily rescue doses over 2 days interval not more than 20% of the total daily morphine doses' (Cundiff et al, 1989); 'over a 48-h period, the q12h dose was unchanged, less than two supplemental analgesic doses were taken per day, the dosing regimen for any non-opioids or adjuvants was unchanged, and the patient reported that pain control was acceptable and any side effects were tolerable' (Mucci-LoRusso et al, 1998). Inadequate pain relief was defined as: 'more than two doses of rescue medication/24 h, or moderately severe global pain score' (Stambaugh et al, 2001); 'despite dose escalation, pain intensity rating more than three on a five point VRS' (Wilder- Smith et al, 1994).…”
Section: Pain Description and Assessmentmentioning
confidence: 99%
“…Individual studies showed no difference between CR morphine tablets and IR morphine or other comparators in terms of the therapeutic profile. For example, Cundiff et al 17 showed that CR morphine and IR morphine were equipotent pharmacologically in a parallel-line log ratio assay using dosages and pain scores. The potency of CR morphine relative to IR morphine was 1.08 for pain intensity and 1.03 for pain frequency with 95% confidence limits of 0.93-1.25 and 0.74 -1.3, respectively.…”
Section: Resultsmentioning
confidence: 99%